Preparation and Characterization of Silver and Gold Nanoparticles and Study Influence on Physical Properties of PVA/PVP nanocomposites - Abdelghany, A. M.; S. Meikhail, Mahrous.; ALdhabi, A. A. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Gold nanoparticles (Au NPs) and Silver nanoparticles (Ag NPs) ware prepared by green synthesis extraction using the Chenopodium murale leaf extract, the obtained (Ag NPs and Au NPs) were investigated by UV/Vis. absorption spectroscopy, transmission electron microscopy, Zetasizer, XRD. The plant extraction leads to produce nanoparticles of spherical shape with size range from 4 to 22 nm. Polyvinyl alcohol (PVA) and polyvinyl Pyrolidone (PVP) blend with mixed silver and gold nanoparticles were prepared by casting method. Amorphous feather of doping polymers blend was characterized by X-ray diffraction. Significant changes within the polymer matrix were monitored from infrared spectroscopy which indicates the interaction between polymer blend and mixed nanoparticles. Both indirect and direct optical energy gaps are calculated and discussed.